Kepentingan Pengajian Al-Quran dalam Membangunkan Peradaban: Kajian Kes dalam Kelas Pengajian Al-Qur’an, Tajwid & Bahasa Arab untuk Awam di Pusat Bahasa (CELPAD), UIAM - amir, ahmad nabil (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
This paper investigates the significance of Qur’anic studies and its science in developing Islamic civilization. To acquire sufficient data and material for study, case study was conducted in Kelas Pengajian Al-Qur’an, Tajwid & Bahasa Arab organized by Centre for Language and Pre-University Academic Development (CELPAD), IIUM. It surveys the pedagogical method and technique assigned in class, and its effectiveness in instilling public consciousness of the underlying value of the Qur’an and its significance to empower individual and society. The method of study is based on observation, and interviews with trainers and participants to see their level of understanding on the significance of class in fostering religious consciousness and establishing rigorous ummah. Generally, the class has effectively promotes value and religious input and increase participants’ understanding of the science of the Qur’an. In this regards, continuous effort must be developed emphasizing on the aspect of reform on the curriculum framework and syllabus. This is set forth in this paper by envisaging reform, and reconstruction through integration of curriculum with contemporary science and thought to increase the standard of learning and teaching process. Summarily, with obvious consequence of the effectiveness of organizing Qur’anic class for the public, this initiative must be expanded more profoundly to produce Qur’anic generation that were instrumental in constructing progressive civilization for the ummah.